Study on the Effect of several concentrations of Antitranspirants , Salicylic acid and Irrigation Intervals on the density and distribution of stomata on the epidermis of Maize (zea mays L.) Cultivated in Diwanyia - Maha Ali Abdulameer ,et.al (Al-Qadisiyah Journal of Pure Science, 2017)
The present experiment was conducted during the autumn of the year (2012) in the city of Al-Diwanyia (Iraq). The goal of the experiment was to find the effect of different types of Antitranspirants (each type with two Concentrations), Salicylic acid (with and without treatment) and irrigation intervals (5, 10 and 15 days), and their interactions on the density and distribution of stomata on the epidermis of maize (zea mays L.)The experiment was designed in a randomized complete blocks (RCBD), in a Factorial arrangement (3*2*7) with three replications. The Revised Least Significant Difference (RLSD) at 0.05 probability level was used to compare treatments means, whenever significant effects were evident.The Antitranspirants and Salicylic acid (first treatment) as well as irrigation intervals were applied at (4- 5 fully expanded leaves) stage. While the second application of Antitranspirants and Salicylic acid, was after a month, at the beginning of tasseling ( 50%). Stomatal frequency and Stomatal index were measured and Results showed:1- The use of Reflectant antitranspirants (Kaolin and Magnesium carbonate) decreased Stomatal frequency and Stomatal index for both abaxial and adaxial epidermis, While the stomatal density increased when the antitranspirant sodium salicylates was used.2- Foliar application of Salicylic acid increased Stomatal frequency for both abaxial and adaxial epidermis and Stomatal index for adaxial epidermis., while it didn’t affect the Stomatal index of the abaxial epidermis.3- Both Stomatal frequency and Stomatal index increased as the irrigation interval increased, and the irrigation of 10-day interval recorded higher Stomatal frequency and Stomatal index for abaxial epidermis while the irrigation of 15-day interval had a Significant impact on the adaxial epidermis.4- Triple interaction between the three factors included in the experiment revealed significant effect on all parameters studied